3(y-6)=25

Simple and best practice solution for 3(y-6)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-6)=25 equation:



3(y-6)=25
We move all terms to the left:
3(y-6)-(25)=0
We multiply parentheses
3y-18-25=0
We add all the numbers together, and all the variables
3y-43=0
We move all terms containing y to the left, all other terms to the right
3y=43
y=43/3
y=14+1/3

See similar equations:

| 20-5w=5 | | 6x^2-24x+8=0 | | 0.3+y=1.7 | | 7/3u=-14 | | 5x+11=2x+29 | | 4(x-2)-7x=0 | | x-2.99=84.1 | | 9=-3/5y | | 1.9+v=2.9 | | -14/9=-7y | | -2(w+3)+3w=0 | | -40+x=-95 | | (n÷n-2)+(1÷n²-4)=(3n-1)÷(3n+6) | | 8x/6+32/6=x+5 | | -5+x=29 | | -6/7=9/7t | | -34=x-14 | | 3(w+2)-5w=0 | | (5x-3)^2=47 | | 32=x- | | (5y-17-10)=153 | | (x+10)=(3x-24) | | 15h=0 | | 16+8u=0 | | x=x+25÷4 | | 4(5+2x=7(x-2) | | 5w−8/3=4w+2 | | x=x+24+1×4 | | 108+h=1 | | 3x+2(x+4=-7 | | x=4(24+1) | | 2t-6=18-8 |

Equations solver categories